JUDICIAL DEBATE IN CRIMINAL PROCEEDINGS AS A WAY OF EXPRESSING THE INTERESTS OF THE PARTIES TO THE CONFLICT - Adygezalova, Gyulnaz; Faroi, Tatyana; Mikhel, Dina; Lukozhev, Husen (Revista Inclusiones, 2020)
The purpose of this work is to study judicial debate as an independent stage of criminal proceedings, which has its procedural goals and objectives, as well as techniques and methods for their solution. General scientific methods were used in the course of the study, including historical, comparative, and logical. The formal legal method was used as well. The study has shown that the legal definition of judicial debate as an independent stage of criminal proceedings, clearly defining the form and content of judicial debate, is necessary. At present, the legislator only points out what judicial debate consists of.